The Emerald handbook of the sociology of emotions for a post-pandemic world : imagined emotions and emotional futures - Ward, Paul R.; Foley, Kristen (Emerald Publishing Limited, 2023)
The study of how emotions are socially patterned is a young and promising field within sociology. This handbook offers a sociological examination of the lived impacts of the COVID-19 pandemic through culture(s) of emotion - from hope to anger, optimism to grief, and courage to boredom. The Emerald Handbook of the Sociology of Emotions for a Post-Pandemic World considers the dynamics and structures of affect as they have been experienced by local and global populations in a time of global health crisis. Advancing a theoretical agenda in the sociology of emotions and drawing from empirical evidence of emotional impacts, the authors cover a range of philosophical and methodological questions about how to study emotions, and why doing so is critical in turbulent times. Including policy and planning insights for how to reconcile our emotional lives and collective experiences in a post-pandemic world, this collection is a refreshing contribution to a new and exciting sub-discipline; and is a compelling read for theorists, researchers, and students of the social, cultural, and political sciences.